Finansiële beoordeling van landboukoöperasies - W. D. Hamman; I. J. Lambrechts; F. J. Mostert (South African Journal of Business Management, 1988)
– This article covers a financial evaluation of 31 representative agricultural co-operatives. Although the ratio of the members' interest to the total assets remained reasonably constant during the study period, the share capital and reserves decreased relatively to the total assets. According to the financial evaluation, it is clear that there is a high gearing ratio, because about 75% of the total capital structure consists of loan capital. Although the asset structure showed no substantial change, the composition of current assets (which represented about 75% of the total assets) changed significantly. The debtors increased considerably whilst a decrease in the inventory cancelled this increase. Therefore it is apparent that the co-operatives fulfil the functions of financial institutions to a large extent. Looking at the liquidity position, the current assets increased relatively to the current liabilities, while a defensive financing policy was applied because the fixed assets, investments and intangible assets were financed by long-term capital. An analysis of the turnover ratios showed that the amounts of the total assets, debtors and current assets increased more rapidly than the sales volume, which may be the result of a more liberal credit policy towards members, the drought in certain parts of the country as well as an over-capitalization of the co-operatives. Although the average profitability was rather low, it must be seen against the background of a service rendered instead of a striving towards a profit. According to available information, it appears that the ability to meet their interest obligations deteriorated seriously since 1982.
Keywords: 650